Facile and gentle method for quantitative lysis of Escherichia coli and Salmonella typhimurium. - Crabtree, S (1984)
Garrett et al. (Mol. Gen. Genet. 182:326-331, 1981) constructed strains of Escherichia coli harboring derivatives of plasmid pBR322 that carry the lysis genes (S, R, and Rz) of phage lambda. The plasmid construction placed the genes under control of the lactose operon operator-promotor (and thus of lac repressor). Induction of E. coli strains carrying these plasmids resulted in rapid lysis of the culture unless the S gene was defective, in which case the cells grew normally. A freeze-thaw treatment of induced cells carrying an S- plasmid gave quantitative lysis of either E. coli or Salmonella typhimurium cells under exceptionally gentle conditions. The method was equally effective on exponential phase cells and stationary phase cells and was readily extended to a large number of independent cultures.